Studi Deskriptif Kompetensi Sosial Guru dalam Pendidikan Islam Perspektif Tafsir Al Qur’an - Qomariyah, Siti; Wendy Asswan Cahyadi; Yurna; Mohammad Lisanuddin Ramdlani; Lupiyanto (LP. Ma'arif Janggan Magetan, 2022)
The low quality of education in Indonesia is caused by poor infrastructure and incompetent teachers. The purpose of this study was to determine the social competence of teachers in Islamic education from the perspective of the Al-Qur'an interpretation. This research is library research, with the descriptive method of qualitative analysis. The researcher describes the Teacher's Social Competence in Islamic Education and then analyzes it in detail and depth with the Al-Qur'an Tafsir Perspective. Namely the book of Tanwir Miqbas Min Tafsir Ibn Abbas, Tafsir Jalalain, Tafsir al Qur'an al Azim, al Jawaahir al Hisan fii Tafsir al Qur'an, al Jamii 'li Ahkaam al Qur'an. The results of this study are competent teachers, namely teachers who master various sciences related to their responsibilities. Social competence is the ability of teachers in good associations and communication with the school, community and family. Communication must be built with unity, mutual help, advising each other in kindness and patience, easy to thank, good at being grateful, stay away from deceit, care for the poor, tolerance, simple, not arrogant, non-discriminatory and prohibited from spying, having bad attitudes and reproach.